2004
DOI: 10.1063/1.1769366
|View full text |Cite
|
Sign up to set email alerts
|

Binding of propene on small gold clusters and on Au(111): Simple rules for binding sites and relative binding energies

Abstract: We use density functional theory(DFT) to investigate the bonding of propene to small gas-phase gold clusters and to a Au(111) surface. The desorption energy trends and the geometry of the binding sites are consistent with the following set of rules.(1) The bond of propene to gold is formed by donation of electron density from the highest occupied molecular orbital (HOMO) of propene to one of the low-lying empty orbitals [denoted by LUMO1, LUMO2, … (LUMO-lowest unoccupied molecular orbital)] of the gold cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
73
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 72 publications
6
73
0
Order By: Relevance
“…7 The attention to these catalysts has not diminished, as is evidenced by the number of reports published by many groups over the last year. [8][9][10][11][12][13][14][15][16][17][18][19][20] Despite all of this attention, the mode of operation of these catalysts is still under discussion, especially for the epoxidation of propene. Both gold and titania seem to be a necessity for a catalyst to be able to epoxidize propene.…”
Section: Introductionmentioning
confidence: 99%
“…7 The attention to these catalysts has not diminished, as is evidenced by the number of reports published by many groups over the last year. [8][9][10][11][12][13][14][15][16][17][18][19][20] Despite all of this attention, the mode of operation of these catalysts is still under discussion, especially for the epoxidation of propene. Both gold and titania seem to be a necessity for a catalyst to be able to epoxidize propene.…”
Section: Introductionmentioning
confidence: 99%
“…In two previous papers 1,2 we have studied the adsorption of propene on small Au and Ag clusters. We have found there a number of ''empirical'' rules that allow us to guess the relative desorption energy and the binding site of the propene, from the shape and the energy of the lowest unoccupied molecular orbital ͑LUMO͒ of the ''naked'' metal cluster.…”
Section: Introductionmentioning
confidence: 99%
“…5 where it can be observed that the maximum of the Fukui function is always in the positions where the hydrogen atom binds. It seems that the f Ff ± is, in part, a quantitative application of the rules proposed by Chrétien et al 21,22 Next, it is important to assess the quality of the obtained results. Therefore, the total energy and the binding energy per atom, BE= ͓E͑Si n H͒ − nE͑Si͒ − E͑H͔͒ / n, of all the clusters have been calculated using the already presented B3LYP/ 6-311+ + G ** , the LSDA/ 6-311+ + G ** , and the MP2 / 6-311+ + G ** methodologies.…”
Section: Resultsmentioning
confidence: 99%
“…19 Galvan et al have studied the reactivity of Si 4 with a single atom ͑Si or Ga͒ 20 using the reactivity indices defined in the density-functional theory ͑DFT͒. The topology of the frontier orbitals were used by Chrétien et al 21,22 to propose simple rules which can be used to predict the binding site of propene to Au and Ag clusters. Mañanes et al 23 have used the topology of the Fukui function and the atomic condensed Fukui function analysis to study the bonding and reactivity of H and Al 13 clusters.…”
Section: Introductionmentioning
confidence: 99%